A Narrative Review of Empirical Literature of Behavioral Activation Treatment for Depression - Wang, Xiaoxia; Feng, Zhengzhi (Frontiers in Psychiatry, 2022)
Grounded in the profound tradition of behaviorism theory and research, behavioral activation (BA) has become a standalone psychotherapy for depression. It is simple, straightforward, and easy to comprehend, with comparable efficacy to traditional CBT, and has developed into an evidence-based guided self-help intervention. The main work in the theoretical models and treatment manuals, as well as empirical evidence of the effectiveness of BA for (comorbid) depression in primary and medical care setting are introduced. With the rise of the third wave of CBT, therapeutic components across diagnoses will be incorporated into BA (e.g. mindfulness). Extensive studies are required to examine the neurobiological reward mechanism of BA for depression, and to explore the feasibility and necessity of e-mental health BA application into the public healthcare system in China.